Sociocultural dynamics that influence chagas disease health care in Colombia (2020)
Chagas disease (CD) is a Latin America endemic and neglected tropical disease that affects primarily poor people living in rural areas. Its current low profile leads to many diagnostic, treatment, and control challenges. This study aimed to identify and characterize the sociocultural dynamics that influence CD health care in Colombia. Data for our ethnographic study was collected in 2013 and included participant observation in two main endemic areas in Colombia. In addition, 81 people belonging to four groups (patients and family members; health care workers; researchers; and officers) were recruited through snowball sampling technique and participated in informal and semi-structured interviews. People from the first two groups also participated in social cartography excercises. Data analysis resulted in the identification of three main sociocultural dynamics. Local Understandings: Patients reported confusions around disease transmission, treatment effectiveness and development of future complications. Providers' Knowledge and Training: Failures in professional's knowledge and training mostly affect the primary level of care in rural areas. Professionals undergo minimal training during medical school and lack access to continuous education. In contrast, clinicians working at tertiary university hospitals or at the CD unit of the Colombian National Institute of Health (NIH) exhibited great knowledge and competency. Health Care System Barriers: The Colombian market-based health care reform augmented access barriers, which impacted CD care greatly. We identified geographic and bureaucratic itineraries that depended on type of insurance plan, insurance contracts with service providing institutions, and levels of care. This study shows that people's experience of these sociocultural dynamics vary depending on their mobility from rural to urban contexts. It unveils the importance of analyzing the structure of the health care system. In the Colombian case, its for-profit orientation has become one of the most important obstacles for comprehensive, integrated, and timely health care responses.